Child welfare inequalities: new evidence, further questions. Issue 3 (8th May 2014) - Bywaters, Paul; Brady, Geraldine; Sparks, Tim; Bos, Elizabeth
Abstract: Research internationally has identified large differences in rates of child safeguarding interventions, recently characterized as child welfare inequalities, markers of social inequalities in childhood with parallels to inequalities in health and education. This paper reports a Nuffield Foundation‐funded study to examine the role of deprivation in explaining differences in key children's services interventions between and within local authorities (LAs). The study involved an analysis of descriptive data on over 10% of children on child protection plans or in out‐of‐home care in 14 English LAs at 31 March 2012. The data demonstrate very large inequalities in rates of child welfare interventions within and between LAs, systematically related to levels of deprivation. There is evidence of a gradient in child welfare inequalities across the whole of society. There also appears to be an equivalent of the inverse care law for health: For any given level of deprivation in local neighbourhoods, LAs with lower overall levels of deprivation were intervening more often. The findings raise fundamental questions for research, policy and practice including whether the allocation of children's service resources sufficiently recognize the impact of deprivation on demand and how we judge whether a safeguarding system is effective at the population level.